O tempo bom do farol: transgressão, sociabilidade e afeto nas trajetórias de ex-prostitutas idosas - Pinho, Érika Bezerra de Meneses (2012)
O tempo bom do Farol": Transgression, sociability and afection in trajectories of elderly former prostitutes. Resumo This dissertation was built upon narratives of stories of elderly women's lives who worked as prostitutes in the area known as Farol do Mucuripe, in Fortaleza, from 1960 to 1980. For this work, were used methods of oral history, combined with ethnographic strategies, such as the interpretation of cultural meanings and practices presented in the speeches of the interviewees, as well as the presence of the researcher in the district of Serviluz, where they reside, in order to create a network of relationships favorable to the development of this research. The contents of the speeches were the basis for the choice of central categories of the final analysis, namely the characteristics of sociability in that prostitutional context, the supposed transgressive aspect of the practices and discourses and the presence of affect as a component of the modality of prostitution described by the interviewees. Confronted with restrictive models to the experience of womanhood, the women surveyed were part of the collective construction of a sui generis way to become a woman, in which the personal efforts were directed to the search for subjective autonomy. Throughout this process, however, the characters in this study maintained compliance with traditional values ​​about sexuality and the role of women in society. It is concluded that the practice of prostitution in red-light area known as Farol, during the reported decades, helped to strengthen the established morals. Thus, the existence of a specific place for sexuality outside the institution of marriage allowed that the noncompliance of social norms occurred in an organized and non-transgressive way.